PENINGKATAN PAJAK DAN RETRIBUSI KEDAI KOPI DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KOTA BANDA ACEH - Muzakkir Muzakkir (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2015)
As an effort to fulfill and in crease local own source revenue , Banda Aceh government through the Department of Finance and Asset Management Areas also do the collection taxes and retribution to the coffee shop s in Banda Aceh The purpose of this study is determine how the effect of tax es and retribution waste services cleanliness of the coffee shop to the local own source revenue PAD) of Banda Aceh The data was used in this study is a time series data during 2008 to 201 3 from January to December of data include: taxes and retributio n waste services / cleanliness of the coffee shop in Banda Aceh and the local own source revenue PAD) of Banda Aceh subsequently analyzed using Ordinary Least Square (OLS). The goal to this study should note that all the independent variables , namely tax coffee shops and retribution of waste services hygiene provide a statistically significant effect on local own source revenue PAD) of Banda Aceh by 50.12 %. Tax CafÃ© a positive impact on revenue of Banda Aceh at 18 336 and cleaning levy of 352.54.